Aligning lyotropic liquid crystals with unconventional organic layers - Otón, Eva; Geday, Morten Andreas; Tone, Caterina Maria; Otón, José Manuel; Quintana, Xabier (Photonics Letters of Poland, 2017)
Lyotropic chromonic liquid crystals (LCLC) are a kind of LCs far less known and more difficult to control than conventional thermotropic nematics. Nevertheless, LCLCs are a preferred option -often the only one- for applications where hydrophilic materials must be employed. Being water-soluble, LCLC can be used in numerous biology related devices, for example in target detection in lab-on-chip devices. However, their properties and procedures to align them are still less explored, with only a very limited number of options available, especially for homeotropic alignment. In this work, novel organic alignment layers and alignment properties have been explored for selected LCLCs. Non-conventional organic alignment layers were tested and new suitable procedures and materials for both homogeneous and homeotropic alignments have been found. Full Text: PDF References S.L. Hefinstine, O.D. Lavrentovich, C.J. Woolverton, "Lyotropic liquid crystal as a real-time detector of microbial immune complexes", Lett. Appl. Microbiol. 43, 27 (2006). CrossRef M.A. Geday, M. Ca-o-García, J.M. Escolano, E. Otón, J.M. Otón, X. Quintana, Conference on Liquid Crystals CLC’16, Poland (2016). M.A. Geday, E. Otón, J.M. Escolano, J.M. Otón, X. Quintana, Patent WO 2015193525 (2015). DirectLink Yu.A. Nastishin et al., "Optical characterization of the nematic lyotropic chromonic liquid crystals: Light absorption, birefringence, and scalar order parameter", Phys. Rev. E, 72 (4) 41711 (2005). CrossRef A. Mcguire, et al., "Orthogonal Orientation of Chromonic Liquid Crystals by Rubbed Polyamide Films", Chem. Phys. Chem. 15 (7) (2014). CrossRef J. Jeong, et al., "Homeotropic Alignment of Lyotropic Chromonic Liquid Crystals Using Noncovalent Interactions", Langmuir 30(10) 2914 (2014). CrossRef J.Y. Kim, H.-Tae Jung, "Macroscopic alignment of chromonic liquid crystals using patterned substrates", Phys. Chem. Chem. Phys. 18, 10362 (2016). CrossRef E. Otón, J.M. Escolano, X. Quintana, J.M. Otón, M.A. Geday, "Aligning lyotropic liquid crystals with silicon oxides", Liq. Cryst. 42 (8) 1069 (2015). CrossRef H.S. Park, et al., "Condensation of Self-Assembled Lyotropic Chromonic Liquid Crystal Sunset Yellow in Aqueous Solutions Crowded with Polyethylene Glycol and Doped with Salt", Langmuir 27, 4164 (2011). CrossRef H.S. Park, et al., "Self-Assembly of Lyotropic Chromonic Liquid Crystal Sunset Yellow and Effects of Ionic Additives", J. Phys. Chem. B 112, 16307 (2008). CrossRef R Caputo et al., "POLICRYPS: a liquid crystal composed nano/microstructure with a wide range of optical and electro-optical applications", J. Opt. A: Pure Appl. Opt. 11, 024017 (2009). CrossRef